Microbiological Analysis of Ice-cream Sold in Kathmandu Valley - Thapa, Krishtina; Shrestha, Sonu (Journal of Food Science and Technology Nepal, 2014)
Different types of ice cream samples were collected from three different local vendors of Kathmandu (i.e. Samakhusi, Jawalakhel and Chabahil) for the microbial examination. Study explored that the ice cream samples from Chabahil showed the presence of highest number of mesophilic microorganisms with an average of 2.16×107 CFU/ml and 27.4 CFU/100ml of Coliform followed by samples collected from Jawalakhel and Samakhusi. The samples have been found to be contaminated with Coliforms (Enterobacter spp., Escherichia spp., Klebsiella spp., Citrobacter spp.), Salmonella (Salmonella typhi, Salmonella paratyphi, Salmonella enteritidis), Shigella (Shigella boydii, Shigella flexneri, Shigella sonnei, Shigella dysenteriae) and Staphylococcus aureus. These findings indicated that not only the unhygienic practices of handling by the vendors but also the carelessness of manufacturers during processing of ice creams. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.10615 J. Food Sci. Technol. Nepal, Vol. 7 (90-92), 2012